Sustainable HR Practices in Indonesian MSMEs from a Social Entrepreneurship Perspective: Training, Recruitment, Employee Engagement, Social Impact of Local Communities - Iskandar, Yusuf; Pahrijal, Rival; Kurniawan, Kurniawan (International Journal of Business, Law, and Education, 2023)
This study looks into the complex interactions that exist between Indonesian Micro, Small, and Medium-Sized Enterprises (MSMEs) and training, hiring, employee engagement, social entrepreneurship performance, sustainable business practices, and the social impact on local communities. The study employs Structural Equation Modeling (SEM-PLS) through a quantitative analysis encompassing 487 MSMEs to explore a broad range of hypotheses. The findings highlight the paradoxical relationship that exists between sustainability and training, underscoring the necessity for HR procedures to be approached with delicacy. High employee engagement and successful hiring emerge as key factors that influence the performance of social entrepreneurship and sustainable business practices. Moreover, the research highlights the positive effects of MSMEs involved in social entrepreneurship on sustainable practices and the larger community, underscoring the connection between sustainability and social entrepreneurship. While the practical consequences direct strategic HR planning and the reform of training programs, the theoretical implications cover the advancement of Sustainable Human Resource Management (SHRM) and the enrichment of social entrepreneurship theory. The research offers significant perspectives for MSMEs aiming to harmonize HR procedures with sustainability goals and promote constructive societal influence.